Application of Diversion in Handling Criminal Acts by Children in the Blitar Police Criminal Investigation Unit (Advances in Police Science Research Journal, 2024)
The aim to be achieved in this research is to find out about the application of diversion problem in handling criminal acts by children in the Blitar Police Criminal Investigation Unit. The method used in this research is descriptive qualitative. This research was carried out in the jurisdiction of the Blitar Police because it was based on institutional policy which divides the areas for carrying out research for each Police Academy cadet. The data collection technique used was conducting interviews, observations, and documentation. The results of this study indicate that the issue in implementing diversion by the Blitar Police Resort in resolving crimes committed by minors is the low number of cases successfully resolved through diversion. Out of 21 cases of juvenile delinquency at the Blitar Police Resort from 2020 to November 2023, only 4 cases, or 19% of the total, were successfully resolved through diversion. This could be influenced by the prevailing perception in society that offenders must be punished to deter future offenses. The internal factors that have the power to influence the investigation process in cases of children in conflict with the law are the motivation of members, dedication and discipline in completing the tasks assigned well, and good use of the budget. Meanwhile, the weaknesses are the limited number of personnel and no one has taken vocational education, limited facilities, there is no special detention room at the Blitar Police. External factors that provide opportunities for coordination with BAPAS, and the culture of community mutual cooperation that influence implementation diversity. Meanwhile, the threat factor is that child perpetrators are prone to excessive fear, negative stigma from society, and the victim who does not forgive the perpetrator.
Keywords: Diversion; Children; Criminal Act; Blitar Police